Analisis Sustainability Literacy (Literasi Keberlanjutan) Peserta Didik Fase E pada Isu Bioteknologi di SMAN 12 Padang: Penelitian - Dini Destria Nova Putri; Rahmawati D; Muhyiatul Fadilah; Fitri Olvia Rahmi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Poverty literacy is an important ability in supporting the achievement of sustainable development goals (SDGs), which includes aspects of knowledge, knowledge skills, and mindset. This study aims to analyze the literacy of the arrival of phase E students on biotechnology issues at SMAN 12 Padang. This study is a descriptive study with a quantitative approach. The sampling technique for this study was carried out randomly using a simple random sampling technique. The research sample consisted of 196 students spread from Phase E1 to Phase E11. The instrument used was a multiple-choice test question related to biotechnology issues that referred to the desire literacy indicator. The results of this study indicate that the literacy of the arrival of students at SMAN 12 Padang is classified as very low at 51.80%. Based on the analysis of the interest literacy aspect, it can be seen that in the knowledge aspect there is a value of 45.04%, in the knowledge skills aspect with a value of 60.40%, and the mindset aspect with a value of 53.23%. Therefore, it can be concluded that the desire literacy of students in Phase E at SMAN 12 Padang is still very low.